Undernutrition screening survey in 564, 063 patients: patients with a positive undernutrition screening score stay in hospital 1.4 d longer. Issue 4 (9th March 2016) - Kruizenga, Hinke; van Keeken, Suzanne; Weijs, Peter; Bastiaanse, Luc; Beijer, Sandra; Huisman-de Waal, Getty; Jager-Wittenaar, Harriët; Jonkers-Schuitema, Cora; Klos, Mariël; Remijnse-Meester, Wineke; Witteman, Ben; Thijs, Abel
ABSTRACT: Background: Undernutrition is a common complication of disease and a major determinant of hospital stay outcome. Dutch hospitals are required to screen for undernutrition on the first day of admission. Objective: We sought to determine the prevalence of the screening score "undernourished" with the use of the Short Nutritional Assessment Questionnaire (SNAQ) or Malnutrition Universal Screening Tool (MUST) and its relation to length of hospital stay (LOS) in the general hospital population and per medical specialty. Design: We conducted an observational cross-sectional study at 2 university, 3 teaching, and 8 general hospitals. All adult inpatients aged ≥18 y with an LOS of at least 1 d were included. Between 2007 and 2014, the SNAQ/MUST score, admitting medical specialty, LOS, age, and sex of each patient were extracted from the digital hospital chart system. Linear regression analysis with ln(LOS) as an outcome measure and SNAQ ≥3 points/MUST ≥2 points, sex, and age as determinant variables was used to test the relation between SNAQ/MUST score and LOS. Results: In total, 564, 063 patients were included (48% males and 52% females aged 62 ± 18 y). Of those, 74% (419, 086) were screened with SNAQ and 26% (144, 977) with MUST, and 13.7% (SNAQ) and 14.9% (MUST) of the patients were defined as being undernourished. Medical specialties with the highest percentage of the screening score of undernourished were geriatrics (38%), oncology (33%), gastroenterology (27%), and internal medicine (27%). Patients who had an undernourished screening score had a higher LOS than did patients who did not (median 6.8 compared with 4.0 d; P < 0.001). Regression analysis showed that a positive SNAQ/MUST score was significantly associated with LOS [SNAQ: +1.43 d (95% CI: 1.42, 1.44 d), P < 0.001; MUST: +1.47 d (95% CI: 1.45, 1.49 d), P < 0.001]. Conclusions: This study provides benchmark data on the prevalence of undernutrition, including more than half a million patients. One out of 7 patients was scored as undernourished. For geriatrics, oncology, gastroenterology, and internal medicine, this ratio was even greater (1 out of 3–4). Hospital stay was 1.4 d longer among undernourished patients than among those who were well nourished.